2011
DOI: 10.1039/c0ob01215g
|View full text |Cite
|
Sign up to set email alerts
|

New insights into ergot alkaloid biosynthesis in Claviceps purpurea: An agroclavine synthase EasG catalyses, via a non-enzymatic adduct with reduced glutathione, the conversion of chanoclavine-I aldehyde to agroclavine

Abstract: Ergot alkaloids are indole derivatives with diverse structures and biological activities. They are produced by a wide range of fungi with Claviceps purpurea as the most important producer for medical use. Chanoclavine-I aldehyde is proposed as a branch point via festuclavine or pyroclavine to clavine-type alkaloids in Trichocomaceae and via agroclavine to ergoamides and ergopeptines in Clavicipitaceae. Here we report the conversion of chanoclavine-I aldehyde to agroclavine by EasG from Claviceps purpurea, a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…4; Table 2). As described previously (15), the recipient strain, easA KO A. fumigatus, accumulated primarily chanoclavine and also small quantities of agroclavine (arising via a noncatalyzed isomerization of chanoclavine aldehyde [15,33]) and larger quantities of its oxidation product setoclavine (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…4; Table 2). As described previously (15), the recipient strain, easA KO A. fumigatus, accumulated primarily chanoclavine and also small quantities of agroclavine (arising via a noncatalyzed isomerization of chanoclavine aldehyde [15,33]) and larger quantities of its oxidation product setoclavine (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…benhamiae, Ar. otae and T. verrucosum did not indicate the existence of genes involved in the conversion of chanoclavine-I aldehyde, such as fgaOx3 and fgaFS in A. fumigatus (Wallwey et al, 2010b) or easG in C. purpurea (Matuschek et al, 2011). Furthermore, the genes in the vicinity of the five cluster genes have no significant similarity to known secondary metabolism genes.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the homologous genes responsible for the conversion of chanoclavine-I aldehyde, i.e. fgaOx3 and fgaFS in A. fumigatus (Wallwey et al, 2010b) or easG in C. purpurea (Matuschek et al, 2011), were not found in arthrodermataceous fungi, and nor were further genes in the specific steps of the ergot alkaloid biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include three steps of the basic pathway: apart from dmaW , the genes cloA encoding a cytochrome P450 oxidoreductase, which catalyzes the conversion of elymoclavine to paspalic acid [ 47 ], and ccsA ( easE ) encoding (a component of) the chanoclavine I synthase [ 46 ]. In addition, Matuschek et al [ 52 ] could show by heterologous expression of easG that its product (a dehydrogenase) is involved in the biosynthesis of agroclavine. Much progress has also been made in the analysis of the terminal pathway leading to ergopeptines.…”
Section: Biosynthesis and Molecular Genetics Of Ergot Alkaloidsmentioning
confidence: 98%